2011
DOI: 10.1177/1545109711416509
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Kaposi’s Sarcoma during Primary HIV-1 Infection

Abstract: The majority of cases of Kaposi's sarcoma (KS) occur at low CD4 counts during chronic HIV-1 infection. We present a case of KS which was diagnosed during primary HIV-1 infection. This report aims to draw attention that KS may occur early in the course of HIV-1 infection and that primary HIV-1 infection may rapidly progress to AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
1
1
Order By: Relevance
“…To our knowledge, only a single other case report discusses KS diagnosis during the period of primary HIV infection. However, that patient’s symptoms appeared 11 weeks after HIV diagnosis [14] whereas our patient’s symptoms of Kaposi Sarcoma happened 4 to 5 weeks prior to diagnosis of HIV. Review of the literature revealed a case of an individual diagnosed with AIDS and KS simultaneously [18] .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…To our knowledge, only a single other case report discusses KS diagnosis during the period of primary HIV infection. However, that patient’s symptoms appeared 11 weeks after HIV diagnosis [14] whereas our patient’s symptoms of Kaposi Sarcoma happened 4 to 5 weeks prior to diagnosis of HIV. Review of the literature revealed a case of an individual diagnosed with AIDS and KS simultaneously [18] .…”
Section: Discussioncontrasting
confidence: 55%
“…One month later, he received the biopsy that revealed the additional diagnosis of KS. The patient tested positive Kaposi sarcoma can occur as quickly as 24 months after the primary HIV infection but it is extremely rare to see Kaposi sarcoma during the primary HIV infection [14] . Based on the patient’s clinical presentation, it is most likely that he has classic KS rather than AIDS-related KS.…”
Section: Discussionmentioning
confidence: 93%